Characterization, expression, and functional analysis of polyamine oxidases and their role in selenium‐induced hydrogen peroxide production in Brassica rapa. (18th March 2019) - Wang, Yongzhu; Ye, Xiefeng; Yang, Kang; Shi, Zhiqi; Wang, Ning; Yang, Lifei; Chen, Jian
Abstract: BACKGROUND: Selenium (Se)‐induced phytotoxicity has been linked to oxidative injury triggered by the accumulation of reactive oxygen species (ROS) due to the disturbance of anti‐oxidative systems. However, the way Se stress induces hydrogen peroxide (H2 O2 ) production in plants is a long‐standing question. Here we identified the role of polyamine oxidase (PAO) in H2 O2 production in the root of Brassica rapa upon Se stress. RESULTS: Studying Se‐induced growth inhibition, H2 O2 accumulation, and oxidative injury in the root of Brassica rapa, we found that excessive Se exposure resulted in a remarkable increase in PAO activity. Inhibition of PAO activity led to decreased H2 O2 content and alleviated oxidative injury in the Se‐treated root. These results indicated that Se stress induced PAO‐dependent H2 O2 production. A total of six BrPAO family members were discovered in the genome of B. rapa by in silico analysis. Se stress pronouncedly upregulated the expression of most BrPAOs and further transient expression analysis proved that it could lead to H2 O2 production. CONCLUSION: These results suggest that Se stress upregulates the expression of a set of BrPAOs which further enhances PAO activity, contributing to H2 O2 generation in roots. © 2019 Society of Chemical Industry